2020
DOI: 10.1016/j.triboint.2019.106023
|View full text |Cite
|
Sign up to set email alerts
|

The multiple roles of a chemical tribofilm in hydrogen uptake from lubricated rubbing contacts

Abstract: This is a repository copy of The multiple roles of a chemical tribofilm in hydrogen uptake from lubricated rubbing contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…This novel apparatus enables quantitative measurement of hydrogen permeation from a lubricated contact. This method was employed to study the effect of water contamination, anti-wear and friction modifier additives on tribologically-induced hydrogen uptake from a lubricated interface [13,23].…”
Section: Hydrogen Uptake Measurement Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…This novel apparatus enables quantitative measurement of hydrogen permeation from a lubricated contact. This method was employed to study the effect of water contamination, anti-wear and friction modifier additives on tribologically-induced hydrogen uptake from a lubricated interface [13,23].…”
Section: Hydrogen Uptake Measurement Techniquementioning
confidence: 99%
“…Some of these hydrogen atoms diffuse into the metal membrane and the rest form hydrogen molecules and escape from the surface. Details of this measurement technique can be found in [23].…”
Section: Hydrogen Uptake Measurement Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the wear resistance of titaniummatrix composite (TMC) against M35 steel was improved by adding multilayer graphene (MLG)/Fe 2 O 3 nanocomposite and MLG + Fe 2 O 3 mechanical mixture into base oil, but the addition of MLG or Fe 2 O 3 had no effect [339]. Esfahani et al [340] found that the tribofilm formation of zinc dialkyldithiophosphate (ZDDP) and molybdenum dithiocarbamate (MoDTC), www.Springer.com/journal/40544 | Friction as well as water contamination in oil can impede hydrogen ingress in the steel substrate, by impeding the formation of fresh metal surfaces. This reduces the generation of hydrogen atoms by preventing the decomposition of hydrocarbon molecules.…”
Section: Oxidative Wear and Tribochemical Filmsmentioning
confidence: 99%